Transesterification of palm oil using tungstated zirconia - Nadzirah, Yahya (2010)

(untitled)
The transesterification of unrefined oil using heterogeneous solid acid catalyst is one of the methods of producing biodiesel. Biodiesel is a non- petroleum based fuel thus it has advantages such as non- toxic, biodegradable and environmental friendly. The usage of Tungstated Zirconia will eliminate the drawbacks of using homogeneous catalyst such as corrosiveness, production of waste, and etc. The present studies aimed to determine the conversion of methyl ester produced and the optimum operating condition for the transesterification process. The research study is done in a batch reactor system. The catalyst is activated to 800oC for it to functions at the best state. Optimum operating condition is at 95oC with molar ratio of alcohol to oil is 9:1 and 20 wt% of oleic acid in oil. The highest conversion of methyl ester from this optimum operating condition is 93.14%.